1995
DOI: 10.3109/02841869509093958
|View full text |Cite
|
Sign up to set email alerts
|

Azidothymidine (AZT) as a Potential Modifier of Radiation Response in Vitro

Abstract: The potential effect of AZT as a thymidine analogue on radiation response in vitro was investigated. Two human cell lines (WiDr and HeLa) were used. The effect of 10 microM AZT on exponentially growing cells was studied after different exposure times (24, 48 and 72 h). The surviving fraction (clonogenic assay) or metabolic activity (MTT assay) after irradiation of AZT-exposed cells, was compared to unexposed irradiated controls. Flow cytometry was used to assess the cell-cycle effect of pre-exposure of exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Jagetia and Aruna [25], found that administration of AZT to Hela cells before exposure to different doses of γ-radiation resulted in a significant elevation in the yield of MN. This was in contrast to Copaceanu et al [26] who suggested radioprotection of AZT in Hela cell lines exposed to irradiation in-vitro. Several publications demonstrated that AZT and 3TC alter cell cycle kinetics and increase the proportion of cells in S phase [21,22].…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Jagetia and Aruna [25], found that administration of AZT to Hela cells before exposure to different doses of γ-radiation resulted in a significant elevation in the yield of MN. This was in contrast to Copaceanu et al [26] who suggested radioprotection of AZT in Hela cell lines exposed to irradiation in-vitro. Several publications demonstrated that AZT and 3TC alter cell cycle kinetics and increase the proportion of cells in S phase [21,22].…”
Section: Discussioncontrasting
confidence: 90%
“…Radiosensitivity of cells differs according to cell type and phase of the cell cycle the cells are in at the time of irradiation [37]. In both studies of Jagetia and Aruna [25] and Copaceanu et al [26] irradiations were performed on rapidly-dividing Hela cell lines, while in the current study, lymphocytes were irradiated in the G0 phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our results show that azidothymidine, at concentrations ranging from 3 to 100 mM, decreases cell proliferation, induces an accumulation of T47D cells in the S-phase of cell cycle and can induce the cells to fall into apoptosis. The synchronization in the S-phase, with a concomitant decrease of the percentage of cells in the G0-G1-phase, after incubation with azidothymidine concentrations varying between 0.1 and 200 mM, has been described in different human cell lines (Fridland et al 1990;Roskrow & Wickramasinghe 1990;Chandrasekaran et al 1995;Copaceanu et al 1995;Li et al 1997;Viora et al 1997). Out of these cell lines studied, only MCF-7 cells had been included as representative of human breast cancer (Chandrasekaran et al 1995;Li et al 1997).…”
Section: Discussionmentioning
confidence: 99%